PERAN MANAJEMEN KESISWAAN UNTUK MENINGKATAN MOTIVASI BELAJAR SISWA DI SMAN 1 LEMBAR KABUPATEN LOMBOK BARAT - Rohiyatun, Baiq; Zuliana, Titania Laras; Iqbal, Muhammad (Universitas Pendidikan Mandalika, 2022)
Abstract: One of the components in education management is related to students. Student management aims at organizing various activities that support the achievement of learning outcomes, development of skills, characters, personality and learning motivation of students. This study aims at: 1) analyzing the activities of student management, 2) identifying student management efforts to increase student motivation. 3) and determining the supporting and inhibiting factors in the implementation of student management in order to increase student learning motivation in SMA Negeri 1 Sheet. This research is a qualitative research, with data collection methods using observation, interviews, and documentation. The results shows that: 1) Student management activities in increasing students' learning motivation consist of internal and external activities. The internal activities are to form student discipline in terms of attendance, behavior, dress and worship. While external activities are the activities carried out outside, such as coordinating or collaborating with student councils, participating in science, economics and computer olympiads. 2) Student management efforts to increase student learning motivation, namely: a) it is given for every flag ceremony activity, b) homeroom provides motivation to learn covering all subjects. c) the motivation is given through student discipline. d) the role of counseling teachers in providing learning motivation. e) the motivation is given during religious activities. 3) The supporting factors of the implementation of student management are: a) fulfilled facilities and infrastructure. b) cooperation between teachers is very good. c) modern learning system. d) a comfortable and safe place. While the inhibiting factors: are a) the apathy of the teacher, the teacher's selfishness. b) diverse student backgrounds. c) limited funds for student activities at school. d) the influence of the external environment. e) there are still many students who are not disciplined.Keywords: Student Management, Student Learning Motivation.Abstrak: Penelitian ini bertujuan untuk menganalisis kegiatan dari manajemen kesiswaan di SMA Negeri 1 Lembar. 2) Upaya manajemen kesiswaan untuk meningkatkan motivasi belajar siswa di SMA Negeri 1 Lembar. 3) .Faktor pendukung dan penghambat dari pelaksanaan manajemen kesiswaan dalam meningkatkan motivasi belajar siswa di SMA Negeri 1 Lembar. Penelitian ini menggunakan pendekatan kualitatif, pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian ini sebagai berikut: 1) Kegiatan manajemen kesiswaan dalam meningkatkan motivasi belajar siswa yaitu kegiatan internal dan eksternal. Sedangkan kegiatan eksternal adalah kegiatan yang dilaksanakan di luar seperti berkoordinasi atau bekerja sama dengan osis, mengikuti olimpiade-olimpiade sains, ekonomi dan computer. 2) Upaya manajemen kesiswaan untuk meningkatkan motivasi belajar siswa yaitu: a) motivasi di berikan setiap kegiatan upacara bendera, b) wali kelas memberikan motivasi belajar yang mencakup semua mata pelajaran. c) motivasi diberikan melalu pendisiplinan siswa. d) peran guru BK dalam memberikan motivasi belajar. e) motivasi diberikan pada saat kegiatan keagamaan (Imtaq). 3) Faktor pendukung dan penghambat dari pelaksanaan manajemen kesiswaan yaitu: Faktor pendukung a) sarana dan prasarana yang terpenuhi. b) kerjasama antara guru sangat bagus. c) sistem pembelajaran yang modern. d) tempat yang nyaman dan aman. Sedangkan faktor penghambat a) sifat apatis guru, egois guru. b) latar belakang siswa yang beragam. c) dana yang terbatas untuk kegiatan siswa di sekolah. d) pengaruh lingkungan eksternal. e) masih banyak murid yang tidak disiplin.Kata Kunci: Manajemen Kesiswaan, Motivasi Belajar Siswa